2016
DOI: 10.1080/00986445.2016.1141092
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of Mass Transfer during Leaching of Starch and Protein from Potato

Abstract: In this article, mass transfer during leaching of starch and protein from potato using water as the solvent was investigated. Leaching experiments were carried out by immersion of slab-shaped potato samples in distilled water at 30 C, 45 C, and 55 C, and amounts of starch and protein loss, and moisture gain by the samples were evaluated at different process duration times. A two-parameter model was proposed for prediction of the kinetics of mass transfer and also estimation of the final equilibrium values of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Under these conditions, the product's concentration in the extract rises relatively fast at the early stage of the extraction process and then gradually slows down. It is expected that the value will become constant as the process approaches equilibrium [42].…”
Section: Parametermentioning
confidence: 99%
“…Under these conditions, the product's concentration in the extract rises relatively fast at the early stage of the extraction process and then gradually slows down. It is expected that the value will become constant as the process approaches equilibrium [42].…”
Section: Parametermentioning
confidence: 99%
“…The removal of extractive substances from plant materials is a mass transfer process that occurs in "solid-liquid" system, which requires taking into account the capillary-porous structure of the material [4]. To date, there are a large number of scientific papers devoted to the study of the processes regularities of extractive substances removal from wood raw materials, various approaches to mathematical description of processes and determination of diffusion and mass transfer coefficients [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the microstructure of food material during processing significantly affect solute mass transfer. Whilst some studies have reported that diffusion through a solid matrix is impossible and that diffusion only occurs in the liquid contained in the matrix or via the gas phase [ 22 ], others contend that diffusion through cellular walls and membranes does actually occur [ 24 , 25 ]. Potato tissues act as a physiological barrier to mass and heat transfers, but by heating above 50°C, the cell walls and membranes acting as an ultrafiltration membrane break down.…”
Section: Introductionmentioning
confidence: 99%